Validity and reliability of the Turkish version of the knowledge about childhood autism among health workers questionnaire. Issue 4 (2nd October 2019) - Gürbüz Özgür, Börte; Aksu, Hatice; Eser, Erhan
ABSTRACT: Objective: The aim of this study is to present the psychometric properties of the Turkish version of the knowledge about childhood autism among health workers (KCAHW) questionnaire. Methods: Three hundred fifteen primary health care facility workers and 28 child and adolescent mental health professionals were enrolled in this study. Participants filled out socio-demographic data forms and the KCAHW. Reliability analyses consisted of internal consistency and test–retest reliability. For validity analysis, construct validity (confirmatory factor analysis -CFA) and criterion validity were used. Results: The mean KCAHW questionnaire score was 13.83 ± 2.55. The floor effects in all domains were below 15%, the ceiling effects were over 15% in overall score and in Domain 4. Intraclass correlation coefficient and the Kuder Richardson 21 values were 0.83 and 0.683, respectively; All goodness of fit indices generated by CFA were found satisfactory (Comparative fit index = 0.79; Root mean square error of approximation = 0.056, and chi-square/degree of freedom = 1.91). Being a physician, being a CAMH specialist, having mental health clinic experience, having done a child psychiatry internship, knowing someone diagnosed with autism, follow-up experience of a patient with autism, having previous autism training, and the perception of adequate knowledge about autism, significantly increased the KCAHW scores ( p  < 0.001). Conclusion: The Turkish version of the KCAHW questionnaire is reliable (in terms of test-retest and internal consistency) and valid (sensitive some known/expected external criteria). Due to the insufficient internal consistency in Domain 4, the scores received from Domain 4 should be evaluated with caution.